Technical Note: Imaging dose resulting from optimized procedures with limited‐angle intrafractional verification system during stereotactic body radiation therapy lung treatment - Ding, George X.; Zhang, Yawei; Ren, Lei (Medical physics (Lancaster), 2019)
Purpose The limited‐angle intrafractional verification (LIVE) system was developed to track tumor movement during stereotactic body radiation therapy (SBRT). However, the four‐dimensional (4D) MV/kV imaging procedure results in additional radiation dose to patients. This study is to quantify imaging radiation dose from optimized MV/kV image acquisition in the LIVE system and to determine if it exceeds the American Association of Physicists in Medicine Task Group Report 180 image dose threshold. Methods TrueBeam™ platform with a fully integrated system for image guidance was studied. Monte Carlo‐simulated kV and MV beams were calibrated and then used as incident sources in an EGSnrc Monte Carlo dose calculation in a CT image‐based patient model. In three representative lung SBRT treatments evaluated in this study, tumors were located in the patient's posterior left lung, mid‐left lung, and right upper lung. The optimized imaging sequence comprised of arcs ranging from 2 to 7, acquired between adjacent three‐dimensional (3D)/IMRT beams, with multiple simultaneous kV (125 kVp) and MV (6 MV) image projections in each arc, for different optimization scenarios. The MV imaging fields were generally confined to the treatment target while kV images were acquired with a normal open field size with a full bow‐tie filter. Results In a seven‐arc acquisitions case (highest imaging dose scenario), the maximum kV imaging doses to 50% of the tissue volume (D50 from DVHs), for spinal cord, right lung, heart, left lung, and the target, were 0.4, 0.4, 0.6, 0.7, and 1.4 cGy, respectively. The corresponding MV imaging doses were 0.1 cGy to spinal cord, right lung, heart, and left lung, and 11 cGy to target. In contrast, the maximum radiation dose from two cases treated with two Volumetric‐Modulated Arc Therapy (VMAT) fields and two‐arc image acquisitions is approximately 30% of that of the seven‐arc acquisition. Conclusions We have evaluated the additional radiation dose resulting from optimized LIVE system MV/kV image acquisitions in two best (least imaging dose) and one worst (highest imaging dose) lung SBRT treatment scenarios. The results show that these MV/kV imaging doses are comparable to those resulting from current imaging procedures used in Image‐Guided Radiation Therapy (IGRT) and are within the dose threshold of 5% target dose as recommended by the AAPM TG‐180 report.